2022
DOI: 10.1007/s11115-022-00645-6
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Millennials’ eco-literacy and biospheric values on green purchases: the mediating effect of attitude

Abstract: The objective of this study is to find out the effect of eco-literacy and biospheric values on attitudes and intention to purchase green products. To observe this, we developed a study design that includes variables from green consumer behavior literature. We collected data from 447 respondent of public sector banks using a questionnaire survey. Finally, a model including biospheric values, eco-literacy, attitude and purchase intention was validated with a path analysis. The results of this study disclosed a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 83 publications
0
10
0
1
Order By: Relevance
“…Other researchers have found that Millennials are not only the generation that most identifies with green consumption but also represent a powerful engine in the development of an environmentally conscious population (Nguyen et al, 2017;Ali et al, 2022). Additionally, Millennials tend to support environmental laws, more than any other generation, and agree with friendly policies that favor the environment (Naderi and Van, 2018;Tiwari, 2022). However, despite the growing importance of green consumption in developed economies, it is necessary to promote green purchasing behavior in developing countries (Nguyen et al, 2017;Carri on et al, 2023).…”
Section: Literature Review 21 Green Consumption In Millennialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other researchers have found that Millennials are not only the generation that most identifies with green consumption but also represent a powerful engine in the development of an environmentally conscious population (Nguyen et al, 2017;Ali et al, 2022). Additionally, Millennials tend to support environmental laws, more than any other generation, and agree with friendly policies that favor the environment (Naderi and Van, 2018;Tiwari, 2022). However, despite the growing importance of green consumption in developed economies, it is necessary to promote green purchasing behavior in developing countries (Nguyen et al, 2017;Carri on et al, 2023).…”
Section: Literature Review 21 Green Consumption In Millennialsmentioning
confidence: 99%
“…, 2022). Additionally, Millennials tend to support environmental laws, more than any other generation, and agree with friendly policies that favor the environment (Naderi and Van, 2018; Tiwari, 2022). However, despite the growing importance of green consumption in developed economies, it is necessary to promote green purchasing behavior in developing countries (Nguyen et al.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Previous research has shown that eco-literacy is associated with a greater propensity to select and adopt sustainable, environmentally friendly products and behaviors (Bhutto et al, 2020;Tiwari, 2022;Al Mamun et al, 2020;Shimul and Cheah, 2023). Consequently, eco-literacy can likely increase consumers' propensity to consume organic food.…”
Section: Eco-literacy As Moderatormentioning
confidence: 99%
“…Orr (1992) mentioned term "ecoliteracy" originated, which refers to possessing knowledge about the general well-being of the environment. An ecologically capable society tends to be self-sustaining and refrains from disturbing the natural ecosystem that supports it (Tiwari, 2022). As such, consumers with greater environmental literacy are expected to make sustainable choices such as organic food, which is more environmentally friendly than traditional alternatives (Azzurra et al, 2019;Carri on B osquez et al, 2023), as it is free from artificial ingredients such as chemicals, pesticides, fertilizers and growth hormones (Kumar et al, 2023).…”
Section: Eco-literacy As Moderatormentioning
confidence: 99%
See 1 more Smart Citation